The Current Characteristics of Entrepreneur among Millennials in The Capital City of Indonesia - Teddy, Michael; Sumrahadi, Abdullah; Haji Din, Badariah (UUM Press, 2018)
Many types of research imply young entrepreneur is different from the other entrepreneur that exist. Recently the millennial generations possess more entrepreneurial potential than the previous generation. Some of the millennials believe that to become an entrepreneur could increase their career level and prosperous future. Interestingly about 50% of financial and technology company founders are the millennials, but it appears that the business world is currently being run by millennials is quite difficult to survive compare with the other that already mature in business. The aim of this paper is to explore the characteristics of entrepreneur among the millennial generations at the capital city in Indonesia. This research has been conducted on a group of 80 millennials in Jakarta as one of the capital and creative cities in Indonesia. The results of this study can be used by millennials who want to become an entrepreneur. Furthermore, this research can be used also as a self-screening to understand their entrepreneurial characteristics, before starting a new business.